Profile of Students' Needs Analysis for the E-Module of Statistical Physics on the Topic of Quantum Statistics Applications to Other Systems - Lestari, Neneng; Purwaningsih, Sri; Pratiwi, Intan (Tarbawi : Jurnal Ilmu Pendidikan, 2022)
Lecturers, as facilitators, must effectively fulfill their role in providing instructional materials that enhance students' understanding of the course content. This study aims to analyze students' needs for teaching materials in Statistical Physics, specifically focusing on the application of quantum statistics to other systems. A quantitative survey method was employed for this research. The participants were 50 Physics education students at Jambi University, all of whom had enrolled in the Statistical Physics course. Data were collected through a questionnaire designed to assess students' preferences for the teaching materials they require. The findings reveal that the majority of instructional resources and materials used by instructors are printed textbooks. Furthermore, 94% of students indicated a preference for digital teaching materials, such as e-modules, to facilitate learning. Based on these results, there is a clear need for the development of e-modules as a practical and mathematical resource to address the challenges students face in comprehending Statistical Physics content.